2021
DOI: 10.1111/bpa.13013
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 and the brain: A review of the current knowledge on neuropathology in COVID‐19

Abstract: SARS‐CoV‐2 (severe acute respiratory syndrome coronavirus 2), the new coronavirus responsible for the pandemic disease in the last year, is able to affect the central nervous system (CNS). Compared with its well‐known pulmonary tropism and respiratory complications, little has been studied about SARS‐CoV‐2 neurotropism and pathogenesis of its neurological manifestations, but also about postmortem histopathological findings in the CNS of patients who died from COVID‐19 (coronavirus disease 2019). We present a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 117 publications
(157 reference statements)
4
64
0
1
Order By: Relevance
“…Here, we also performed whole-genome sequencing of this patient (findings of the main COVID-19-associated variants are shown in Additional file 1 : Supplementary Table 3), in addition to the APOE analysis. Microvascular brain injury has been reported to associate with COVID-19 [ 26 ], and autopsied COVID-19 patients have been reported to exhibit micro- and perivascular haemorrhages [ 27 , 28 ] (but see also [ 29 ]). However, we are not aware of any reports associating it with the APOE genotype status.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we also performed whole-genome sequencing of this patient (findings of the main COVID-19-associated variants are shown in Additional file 1 : Supplementary Table 3), in addition to the APOE analysis. Microvascular brain injury has been reported to associate with COVID-19 [ 26 ], and autopsied COVID-19 patients have been reported to exhibit micro- and perivascular haemorrhages [ 27 , 28 ] (but see also [ 29 ]). However, we are not aware of any reports associating it with the APOE genotype status.…”
Section: Resultsmentioning
confidence: 99%
“…Maiese et al [110] indicated that in patients with SARS-CoV-2 infection, the postmortem analyses demonstrated mainly hypoxic changes as the most frequently reported alteration of brain tissue, followed by ischemic and hemorrhagic lesions plus reactive astrogliosis and microgliosis. Since these findings are not specific to SARS-CoV-2 infection, the authors hypothesized a more likely association with systemic inflammation and coagulopathy caused by COVID-19.…”
Section: Precipitating Factorsmentioning
confidence: 99%
“…However, expression of the hACE2 transgene in these mice is nonphysiological with both a high number of hACE2 transgene insertions as well as ectopic expression on cells that do not normally express ACE2. This is best exemplified by SARS-CoV-2 infection in the brains of K18-hACE2 Tg mice, which does not reflect the central nervous system (CNS) involvement seen in humans or other animals such as hamsters or nonhuman primates ( 5 8 ). Because expression of hACE2 in K18-hACE2 Tg mice is independent of the transcriptional regulation that normally governs ACE2 levels, some aspects of infection or transmission likely are not modeled in a physiologically relevant manner.…”
Section: Introductionmentioning
confidence: 99%